Restaurant Transaction Application Based on Android System - Nyoman Ayu Gita Gayatri; Dicky Samuel Santoso; Daryl Andrian; William Yong (ULTIMA InfoSys, 2022)
Abstract - This study was conducted to see the impact of COVID-19 to transactional activity in restaurant, especially for dine in and take away services. This study aims to help people to transact easily, comfortably, and safely in a restaurant. Other than that, this study aims to help restaurant management activity to be better. This study was developed using lead startup method to give a proper solution. Solution was made in a mobile application for android using Flutter technology. The main features of this application are (1) search for merchant and looking at the available capacity, (2) doing reservation, (3) ordering food for dine in and take away, and (4) doing cashless payment systems in the application also help users to reduce contact with waiters and cashiers. Keywords: Restaurant, Technology, transaction, dine in, take away, COVID-19